1996
DOI: 10.1242/jeb.199.8.1743
|View full text |Cite
|
Sign up to set email alerts
|

Mucus Entrapment of Particles by a Suspension-Feeding Tilapia (Pisces: Cichlidae)

Abstract: A miniature fiberoptic endoscope was used to observe the processes of particle encounter and retention inside the buccopharyngeal cavity of suspension-feeding tilapia. Small particles (38 µm to 1.0 mm in diameter) were trapped in strands and aggregates of mucus, which usually slid posteriorly on the ceratobranchials of arches I­IV towards the esophagus while the fish pumped water through the buccopharyngeal cavity. During stage 1 of periodic reversals of water flow inside the buccopharynx, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 56 publications
0
18
0
1
Order By: Relevance
“…The herbivorous black fish's gill rakers direct water toward the oral cavity roof, where food particles are trapped by the mucous covering before being ingested (Sanderson et al 1991). It was suggested that the gill rakers perform a dual function; they change the direction of the water as a first step and filter food particles as a second (Sanderson et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The herbivorous black fish's gill rakers direct water toward the oral cavity roof, where food particles are trapped by the mucous covering before being ingested (Sanderson et al 1991). It was suggested that the gill rakers perform a dual function; they change the direction of the water as a first step and filter food particles as a second (Sanderson et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…While the δ 13 C value of the gills was decreased by nanoplastic exposure, no significant difference was observed following exposure to microplastics (Figures S1 and S2). In bony fish, including medaka, mucus-covered gill structures (e.g., gill rakers) prevent fouling of the filtering apparatus by retaining undesirable or small dietary particles a few micrometers in diameter. Entrapped in mucus aggregate, these microsized particles are transported to the esophagus for ingestion, , preventing the accumulation of microplastics. Although nanoplastics may also be entrapped in the mucus, some portion of nanoplastics would likely bioaccumulate in gill epithelium cells due to the permeability of nanoplastics, , as sediment particles (<500 nm) have been identified intracellularly in salmonid gill epithelial cells …”
Section: Resultsmentioning
confidence: 99%
“…figure 1(e)) [29,62]. Both mucus and protuberances have been hypothesized or demonstrated in experiments with a diverse variety of live suspension-feeding fish to play key roles in particle retention and fluid dynamics [46,63]. Microridges detected on the leading edge of basking shark gill rakers have recently been demonstrated in CFD simulations to have the potential for profound effects on flow patterns during filtration [47].…”
Section: Denticles Microstructures and Surface Propertiesmentioning
confidence: 98%